DEVELOPMENT OF THE UZBEKI NATIONAL STRUGGLE DURING THE YEARS OF INDEPENDENCE - Hayitov Marvarbek; Yusupov Saidaliakbar (TADQIQOTLAR.UZ, 2024)
ABSTRACT: Honor of independence and President I. Thanks to Karimov's wrestling, Uzbek wrestling gained a global status. President I.A. Karimov said, "Today, the work of Uzbek wrestling, which has been the pride of our people since the dawn of time, entered the western arena, and its recognition made us happy." In 1992, the labor force performing this process — The National Wrestling Federation was established. of the Federation of wrestling enthusiasts, whose legal documents have been confirmed A meeting of the stakeholders was held. In general, the development process of the Uzbek country consists of several stages.